"Macaíba, " an emerging oil crop: Nutritional evaluation of the pulp and kernel fruits from semi‐arid and coastal zone of northeast Brazil. (2nd September 2020) - Barbosa da Silva, Raquel; da Silva‐Júnior, Edvaldo Vieira; Trigueiros, Larissa Maria Barreto de Medeiros; Santos, Rayza Helen Graciano dos; Aquino, Jailane de Souza; Campos, Ana Regina Nascimento; de Oliveira, Antônio Fernando Morais
Abstract: Many native species of the Brazilian flora are still little explored economically in the country. An example is Acrocomia intumescens, a palm tree that in recent studies has shown some industrial potential still unexplored. The present study evaluates the proximate composition, including minerals, and total carotenoid content of A. intumescens fruits from three different locations in Pernambuco State, north‐east Brazil, with distinct climatic characteristics. A. intumescens fruits showed that nutritional composition, mineral profile and total carotenoid content varied between fruit parts and between locations. A. intumescens pulp is rich in moisture (35.96%–40.97%), lipids (31.88%–43.22%), ashes (3.63%–4.95%) and total carotenoids (106.69–265.23 µg/g), while the kernel stands out for its high content of lipids (52.08%–56.67%) and proteins (16.49%–21.88%). The main A. intumescens minerals present in the pulp were K (max. 241 mg/100 g) and Mg (max. 153.38 mg/100 g), while P (max. 92.51 mg/100 g) predominated in the kernel. Multivariate analysis (PCA) indicates that location with higher rainfall and temperature produces fruits with higher macro‐ and micronutrient contents.